New Perspectives of Gene Therapy on Polyglutamine Spinocerebellar Ataxias: From Molecular Targets to Novel Nanovectors - Fabiola V. Borbolla-Jiménez; María Luisa Del Prado-Audelo; Bulmaro Cisneros; Isaac H. Caballero-Florán; Gerardo Leyva-Gómez; Jonathan J. Magaña (MDPI AG, 2021)
Seven of the most frequent spinocerebellar ataxias (SCAs) are caused by a pathological expansion of a cytosine, adenine and guanine (CAG) trinucleotide repeat located in exonic regions of unrelated genes, which in turn leads to the synthesis of polyglutamine (polyQ) proteins. PolyQ proteins are prone to aggregate and form intracellular inclusions, which alter diverse cellular pathways, including transcriptional regulation, protein clearance, calcium homeostasis and apoptosis, ultimately leading to neurodegeneration. At present, treatment for SCAs is limited to symptomatic intervention, and there is no therapeutic approach to prevent or reverse disease progression. This review provides a compilation of the experimental advances obtained in cell-based and animal models toward the development of gene therapy strategies against polyQ SCAs, providing a discussion of their potential application in clinical trials. In the second part, we describe the promising potential of nanotechnology developments to treat polyQ SCA diseases. We describe, in detail, how the design of nanoparticle (NP) systems with different physicochemical and functionalization characteristics has been approached, in order to determine their ability to evade the immune system response and to enhance brain delivery of molecular tools. In the final part of this review, the imminent application of NP-based strategies in clinical trials for the treatment of polyQ SCA diseases is discussed.